Ambient vibration response of precast hollow core flooring system - Rahimi, M.I.; Abd. Ghafar, Nor Hayati; Mohd Jaini, Zainorizuan; Ibrahim, Z. (Blue Eyes Intelligence Engineering & Sciences Publication, 2020)
Prestressed precast hollow core is known as a long span slab with a void along its length. The void has a big influence on the weight of the slab. In vibration theory, a lightweight slab with a long span is very sensitive to vibration. In this study, the ambient vibration response of precast hollow core is investigated using the finite element method and modal analysis. Numerical analysis is used to predict the floor vibration and modal testing is used to test the vibration performance of floors on the actual site. The prediction data is obtained by using SAP2000 to determine the vibration behaviour and compared with the modal testing result of the floor located in Kuala Lumpur. The 1st mode shape appeared for 12 natural frequencies between 8.36 Hz to 9.29Hz in the prediction analysis. For modal testing, the vibration behaviour of the actual hollow core floor is determined using an ambient test. The data was obtained using an accelerometer and analysed using Artermis software to determine natural frequencies, damping ratio and mode shape. The 1st mode of natural frequencies for floor area A and area B were 8.45Hz and 9.34Hz. The results from the analysis show that the range of natural frequency between the predicted analysis and that of the modal testing is acceptable. The limitation stated that 10Hz is the cut-off frequency to determine the class of the floor. From the analysis, it is shown that the prediction and the modal testing results are accepted where both floors are classified as low-frequency floors.